Experiences and perceived health benefits of individuals with a disability participating in sport: A systematic review protocol. Issue 11 (24th November 2020) - Aitchison, Beth; Rushton, Alison; Martin, Paul; Soundy, Andrew; Heneghan, Nicola R
Abstract : Introduction: Sports participation has many physical and mental health benefits for individuals with a disability, including improved functionality and reduced anxiety. Despite this, a large proportion of individuals with a disability are inactive. This review will be the first to synthesise the literature on the experiences and perceived health benefits of sport participation for children, adolescents, adults, elite athletes and veterans with a disability. Investigation of these phenomena will enable an understanding of the positive aspects and benefits of sport participation specific to each population, which may help to improve participation rates and ultimately improve health through promotion of these benefits. Methods: A protocol for systematic review is reported in line with Preferred Reporting Items for Systematic Reviews and Meta-Analysis-P. The phenomena of interest are the experiences and perceived health benefits of individuals with a disability participating in sport. There will be no age limit on participants and all study designs, besides reviews, will be included. Studies in languages other than English will be excluded. Two independent reviewers will conduct the searches, study selection, data collection and quality assessment independently. The online databases MEDLINE, EMBASE, PsychINFO, CINAHL Plus, Web of Science and SportDiscus will be electronically searched from database inception to February 2020. Grey literature will be searched and several sport-related journals will be hand-searched. The Quality Assessment Tool for Studies with Diverse Designs will be used for quality assessment of included studies. Thematic synthesis will be used to analyse the qualitative studies, narrative synthesis will be used to analyse the quantitative studies and the perceived health benefits will be analysed using content analysis. The strength of the overall body of evidence will be assessed and reported using GRADE-CERQual (Grading of Recommendations, Assessment, Development and Evaluation–Confidence in the Evidence from Reviews of Qualitative research) for qualitative studies and GRADE for quantitative studies. These approaches will be applied to mixed-methods studies, respectively, where necessary. Ethics and dissemination: This systematic review raises no ethical issues. Results will be published in a peer reviewed journal and disseminated to key stakeholders to inform practice. PROSPERO registration number: CRD42020169224.